Development of a mathematics teaching module based on the APOS model integrated with GeoGebra - Omarisa, Vera; Muchlis, Effie Efrida; Susanta, Agus; Hanifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to develop a mathematics teaching module based on the APOS (Action, Process, Object, Schema) model integrated with GeoGebra, focusing on the topic of quadratic functions for tenth-grade students at SMAN 1 Muara Beliti. The research employed the Plomp development model, which consists of five phases: preliminary investigation, design, construction, validation, and limited testing. The module was developed under the cognitive stages of the APOS model: action, process, object, and schema, and was enhanced through visual exploration using GeoGebra. The research subjects consisted of tenth-grade students and a mathematics teacher at SMAN 1 Muara Beliti, selected through purposive sampling. Data were collected through documentation, expert validation sheets, and practicality questionnaires completed by the teacher and students. The findings indicate that the developed module is highly needed by students and significantly addresses their difficulties in understanding mathematical concepts. Expert validation yielded an average score of 87.85%, classified as highly valid. Practicality testing produced scores of 92.50% from the teacher and 90.41% from the students, both categorized as highly practical. Thus, the module facilitates interactive, conceptual, and contextual learning aligned with the principles of the Independent Curriculum. Accordingly, it is deemed a feasible and innovative instructional resource for high school mathematics learning.